Recepcja twórczości Czesława Miłosza na Litwie - Teresa Dalecka (Postscriptum Polonistyczne)
Research on Czesław Miłosz’s works conducted in Lithuania, although not very intense, is mainly focused on the Lithuanian issues. One major trend prevails among Lithuanian researchers – an attempt to treat a substantial part of Miłosz’s works as autobiographical. Lithuanian translations of the works of Czesław Miłosz were explored in the article. The author poses the question whether works of the Nobel Laureate in any way shape and develop selfawareness of the inhabitants of Lithuania and if they help them to comprehend the diversity of the country as well as its complicated history, multiculturalism and multilingualism.